(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the annotated article the author makes an attempt to compare metaphors in political diskurse from the point of the peculiarities of its usage in modern Ukrainian and Czech social and political journalism.